Pengaruh Proporsi Campuran Buah Pepaya (Carica papaya) Dan Salak (Salaccazalacca) Terhadap Sifat Sensoris dan Kimia Fruit Leather - Masela Ering; Jenny E.A. Kandou; Judith S.C. Moningka; Dekie Rawung (COCOS, 2015)
ABSTRACTFruit is a commodity that has no nutritional value but is easily damaged, so it is necessary to utilize alternative. One such alternative is processed into fruit leather. The raw material of fruit leather can be derived from various types of tropical fruits or subtropical with sufficiently high fiber content. This research aims to produce a mixture of fruit leather from papaya fruit and bark that can be accepted by panelists both the nature of the sensory and chemical properties. This research was conducted at the Laboratory of Food Science and Technology, Faculty of Agriculture Unsrat for Â± 2 months. This study used a completely randomized design with a mixture of papaya and bark treatment. Treatment A = (80% papaya : 20% bark), B = (70% papaya : 30% bark), C = (60% papaya : 40% bark), D = (50% papaya : 50% bark). The results of organoleptic test, the most preferred treatment panelists followed by analysis of the chemical properties of Fruit eather is treated B = (70% papaya : 30% bark). Where the chemical properties of the most preferred Fruit leather panel that has a moisture content 12.46%, total acid 0.38%, and 48.96% total sugars.Keywords: fruit leather, papaya, bark